Evaluation of training manuals for health workers in India in context of kangaroo mother care - Shailaja Daral; Timiresh Kumar Das; Deepti Dabar; Meenakshi Bhilwar; Ravi Prakash Upadhyay (Wolters Kluwer Medknow Publications, 2017)
Background: Kangaroo mother care is an efficacious intervention in preventing mortality in low birth weight babies. With increasing focus on providing home based newborn care in India, it is pertinent to train the frontline healthcare workers in necessary skills for care of low birth weight babies. Objective: The current review was undertaken to evaluate the content of training manuals of frontline health workers in context of care of low birth weight (LBW) babies and Kangaroo Mother Care (KMC). Methods: A systematic extensive internet search was performed to identify training manuals available in public domain, and a targeted search was also done in the websites of Ministry of Health and Family Welfare, Government of India, National Institute of Health and Family Welfare, and National Health System Resource Centre. Manuals published in or after the year 2000 and those in the English language were included in the review. A quality assessment tool was devised and the manuals were finally classified as "poor", "fair", "good" quality. Results: The initial search yielded 107 potentially eligible documents, however, a total of eight training manuals were finally found to be eligible for content evaluation. The mean average score for all the eight manuals was 17.0 (out of a total score of 48) and thus they were "fair" quality (aggregated per cent score of 35.4). Out of the eight training manuals, six had separate section on care of the LBW babies, though content on breastfeeding and skin-to-skin contact was variable. None of the manuals provided case studies/ scenarios or introduced challenges to effective initiation and continuation of KMC. Conclusion: Current training manuals lack quality content on care of LBW babies and KMC and need to be upgraded with evidence-based information.